1968
DOI: 10.1071/bi9681107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Synthesis and Cation Uptake in Beetroot Tissue by Cycloheximide and Cryptopleurine

Abstract: The effects of cycloheximide and of cryptopleurine (two inhibitors of protein synthesis) on ion uptake and protein synthesis in beet disks are described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1970
1970
1981
1981

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The development of ion absorption capacity along with increased respiration has been suggested to involve basic alterations in physiological processes of plant tissue (1,9,14,20,40) and especially in protein metabolism (4,12,20,27). Figure 9A shows results of an experiment on the effect of cycloheximide, a known inhibitor of protein synthesis (4), on the development of K absorption capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of ion absorption capacity along with increased respiration has been suggested to involve basic alterations in physiological processes of plant tissue (1,9,14,20,40) and especially in protein metabolism (4,12,20,27). Figure 9A shows results of an experiment on the effect of cycloheximide, a known inhibitor of protein synthesis (4), on the development of K absorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that by washing slices of aging tuberous roots or stem tissues in various solutions, ion absorption (1,2,15,17,21,30,33,(36)(37)(38), respiratory patterns (14,15,17,19,26,33,38), endoplasmic reticulum (9), protein and RNA metabolism (3,4,12,20,27), and phospholipid turnover in membrane fractions (40) are altered. Plant hormones have also been found to influence the response of isolated tissues as they are aged (30,34,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The It has been repeatedly demonstrated in a wide variety of plant tissues that inhibitors of protein synthesis, such as cycloheximide, will also inhibit energy-linked ion absorption, but the nature of this inhibition is not resolved. In tissues where ion-absorption rates are increasing due to washing or aging (13,17,25,26), the inhibition might be reasonably attributed to blocked synthesis of those enzymes required to augment transport rates. In other cases, however, there have been suggestions that protein synthesis inhibitors may have secondary or side effects, possibly interfering with metabolic energy supply (9,14,22 tions, also blocked IAA-induced growth and its associated increases in respiration, H+ efflux, and cell potential.…”
mentioning
confidence: 99%
“…In tissues where ion-absorption rates are increasing due to washing or aging (13,17,25,26), the inhibition might be reasonably attributed to blocked synthesis of those enzymes required to augment transport rates. In other cases, however, there have been suggestions that protein synthesis inhibitors may have secondary or side effects, possibly interfering with metabolic energy supply (9,14,22).…”
mentioning
confidence: 99%